2015
DOI: 10.1088/2040-8978/17/7/075702
|View full text |Cite
|
Sign up to set email alerts
|

Design of optical time-division multiplexed systems using the cascaded four-wave mixing in a highly nonlinear photonic crystal fiber for simultaneous time demultiplexing and wavelength multicasting

Abstract: This paper reports a new design of optical time-division multiplexed (OTDM) systems that possess a functionality of simultaneous time demultiplexing and wavelength multicasting based on the cascaded four-wave mixing in a dispersion-flattened highly nonlinear photonic crystal fiber (DF-HNL-PCF). A module of OTDM demultiplexing and wavelength multicasting can be feasibly implemented by using a 3 dB optical coupler, a high-power erbium-doped fiber amplifier, a short-length DF-HNL-PCF, and a wavelength demultiplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…However, due to the limited output power of the pump laser used in this study, only 238th order harmonics were observed. It should be noted that the output harmonic pulses exhibited a higher repetition rate and excellent SNR under moderate pump power levels, which is preferable for engineering applications, including ultrahigh‐speed optical time‐division multiplexing systems, [ 46 ] ultrafast all‐optical sampling, [ 47 ] and all‐optical clock recovery. [ 48 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the limited output power of the pump laser used in this study, only 238th order harmonics were observed. It should be noted that the output harmonic pulses exhibited a higher repetition rate and excellent SNR under moderate pump power levels, which is preferable for engineering applications, including ultrahigh‐speed optical time‐division multiplexing systems, [ 46 ] ultrafast all‐optical sampling, [ 47 ] and all‐optical clock recovery. [ 48 ]…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the limited output power of the pump laser used in this study, only 238th order harmonics were observed. It should be noted that the output harmonic pulses exhibited a higher repetition rate and excellent SNR under moderate pump power levels, which is preferable for engineering applications, including ultrahigh-speed optical time-division multiplexing systems, [46] ultrafast all-optical sampling, [47] and all-optical clock recovery. [48] In addition, the performances of the proposed SA and SESAM [49] as well as those of various reported typical 2D SA-based (including graphene, [50] carbon nanotubes, [51] gold nanowires, [52] TIs, [53,54] transition metal dichalcogenides (TMDs), [55][56][57][58] Metal-organic frameworks (MOFs), [59] ferromagnetic insulators, [60] BP, [61] MXenes, [62] bismuthine, [63] tellurene, [64] and antimonene [65] ) passive mode-locking fiber lasers are summarized in Table 1.…”
Section: Harmonic Mode Lockingmentioning
confidence: 99%
“…where, α is the loss coefficient and ( 0 ) = / is the dispersion coefficient of n-th order associated with the propagation constant ( 0 ) extension of the Taylor series around a pump frequency 0 . The first term 0 provides an efficient propagating optical mode index and the second and third terms ( 1 and 2 ) are related to the group velocity and the GVD of the pulse (Chauhan et al 2018;Hui et al 2015).…”
Section: The Principlesmentioning
confidence: 99%
“…where, α is the loss coefficient and 𝛽 𝑛 (𝜔 0 ) = 𝑑 𝑛 𝛽/ 𝑑𝜔 𝑛 is the dispersion coefficient of n-th order associated with the propagation constant 𝛽(𝜔 0 ) extension of the Taylor series around a pump frequency 𝜔 0 . The first term 𝛽 0 provides an efficient propagating optical mode index and the second and third terms (𝛽 1 and 𝛽 2 ) are related to the group velocity and the GVD of the pulse (Chauhan et al 2018;Hui et al 2015).…”
Section: The Principlesmentioning
confidence: 99%